Modeling of an SCN5A founder mutation in iPSC-derived cardiomyocytes. (10th June 2022) - Simons, E; Nijak, A; Vandendriessche, B; Van De Sande, D; Sieliwonczyk, E; Labro, A J; Saenen, J; Snyders, D; Schepers, D; Loeys, B; Alaerts, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research Foundation - Flanders (FWO) Introduction: SCN5A encodes the α-subunit of voltage-gated cardiac sodium channel Nav1.5. Mutations in SCN5A are identified in about 20% of patients with Brugada syndrome (BrS), an inherited cardiac arrhythmia. We have identified an SCN5A founder mutation (c.4813+3_4813+6dupGGGT), leading to a loss-of-function of Nav1.5 in 25 different families. Mutation carriers show variable expression of the phenotype: from asymptomatic to syncopes and sudden cardiac death. We used induced pluripotent stem cell derived cardiomyocytes (iPSC-CM) to investigate the underlying pathophysiology. Material & Methods: Dermal fibroblasts of six patients with different disease severity, and two unrelated healthy control individuals were reprogrammed using a commercially available reprogramming kit. iPSC-CMs were differentiated following a published protocol. We performed several differentiation rounds and investigated expression of cardiac markers using qPCR and immunocytochemistry and electrophysiological properties using patch-clamping. Results: All iPSC-CMs expressed the tested markers. We observed reduction in sodium current density in patient iPSC-CMs compared to the control cells. However, our data display variability in AP characteristics between the differentiation batches, as well as between clones generated from one donor. Conclusions: We established iPSC-CM models for a unique Belgian SCN5A founder mutation. Despite the observed variability, we could detect expected differences in electrophysiological properties of patient cells compared to controls.